Selective electron beam melting of the single crystalline nickel-base superalloy CMSX-4®: From columnar grains to a single crystal - Körner, Carolin; Ramsperger, Markus (Superalloys 2016: Proceedings of the 13th Intenational Symposium of Superalloys, 2016)
Selective electron beam melting (SEBM) is a powder-bed-based additive manufacturing technology. SEBM offers a great potential to process high performance alloys like intermetallics, e.g. TiAl or FeAl, and Ni-based superalloys, which are hard or non weldable materials with high susceptibility to crack-formation. Especially the high process temperatures during SEBM are beneficial for reducing stresses and warpage. In addition, SEBM works under vacuum which guarantees a perfect protection against contamination. In this contribution, SEBM of the single crystalline nickel-base superalloy CMSX-4®1 is investigated. It is shown that crack formation can be avoided by appropriate processing conditions. Regarding the microstructure, SEBM opens the possibility to tailor the microstructure. Whether a columnar grained or a single crystalline grain microstructure is produced depends on the process strategy used. For the first time it is shown, that it is even possible to produce a single crystalline material by an additive powder bed manufacturing process without any grain selector or a seed crystal. The inherent high cooling rates during SEBM lead to a strong reduction of the length scale of the well-known strong segregations in CMSX-4® to some microns. Therefore, long-time and expensive heat treatments are reduced to minutes for a complete homogenization of the single crystal specimen, even for Re. The specimens produced were investigated by using classical optical-metallography techniques and SEM imaging. Complementary microprobe element mappings and EBSD measurements were performed for a detailed analysis of the microstructure.
Keywords: Additive manufacturing; CMSX-4®; Ni-based superalloys; Powder processing; Selective electron beam melting; Single-crystal